New (125)I brachytherapy source IsoSeed I25.S17plus: Monte Carlo dosimetry simulation and comparison to sources of similar design - Pantelis, Evaggelos (Termedia Publishing House, 2013)
PURPOSE: To determine the relative dose rate distribution around the new (125)I brachytherapy source IsoSeed I25.S17plus and report results in a form suitable for clinical use. Results for the new source are also compared to corresponding results for other commercially available (125)I sources of similar design. MATERIAL AND METHODS: Monte Carlo simulations were performed using the MCNP5 v.1.6 general purpose code. The model of the new source was prepared from information provided by the manufacturer and verified by imaging a sample of ten non-radioactive sources. Corresponding simulations were also performed for the 6711 (125)I brachytherapy source, using updated geometric information presented recently in the literature. The uncertainty of the dose distribution around the new source, as well as the dosimetric quantities derived from it according to the Task Group 43 formalism, were determined from the standard error of the mean of simulations for a sample of fifty source models. These source models were prepared by randomly selecting values of geometric parameters from uniform distributions defined by manufacturer stated tolerances. RESULTS AND CONCLUSIONS: Results are presented in the form of the quantities defined in the update of the Task Group 43 report, as well as a relative dose rate table in Cartesian coordinates. The dose rate distribution of the new source is comparable to that of sources of similar design (IsoSeed I25.S17, Oncoseed 6711, SelectSeed 130.002, Advantage IAI-125A, I-Seed AgX100, Thinseed 9011). Noticeable differences were observed only for the IsoSeed I25.S06 and Best 2301 sources.